Influence of a glass fiber mesh on pre-damaged flexible pavement’s fatigue - Kałuża, Mateusz; Kotasiński, Mirosław; Bzówka, Joanna (Archives of Civil Engineering, 2026)
As part of a rehabilitation process, one lane of the pavement was reinforced with glass fiber mesh placed beneath the asphalt layer, while the other lane underwent rehabilitation without the mesh. To evaluate the performance of the pavement, the researchers used Falling Weight Deflectometer (FWD) measurements to assess the layer modulus, which is critical for understanding the structural capacity of the pavement. The fatigue life of the pavement was then calculated and compared against both the measured and predicted traffic load. The results indicated that the application of glass fiber mesh reinforcement positively impacted the pavement’s structural integrity and durability. However, the beneficial effects were only observed after the mining activities that had initially caused damage to the pavement ceased. The pavement’s fatigue life, based on dynamic load and traffic conditions, was compared between reinforced and unreinforced lanes, showing that the reinforced lane exhibited better resistance to damage once mining influences had concluded.